Self-construal and exposure to American entertainment and news programs among Malaysian youths - Tamam, Ezhar; Willnat, Lars; Osman, Mohd Nizam (Universiti Putra Malaysia Press, 2009)
This study examined self-construal (self-independence/self-interdependence) of Malaysian youths, and its relationship with the exposure to American entertainment and news programs. A total of 401 Malay, Chinese and Indian youths participated in the survey by completing the self-administered questionnaires. The results revealed that the respondents exhibited fairly balanced levels of self-interdependence and self-independence. The Malay respondents showed somewhat a higher level of self-interdependence than that of the Chinese and Indians. The respondents who described self primarily in independent, rather than interdependent term, were more likely to have a higher level of exposure to American movies and music. Nevertheless, no significant difference was observed in the exposure to American news programs. The findings supported the contention on the role of self-construal in explaining the variation in the consumption of American movies and music among the youth in a non-western country.